Prognostic factors for clinical failure of exacerbations in elderly outpatients with moderate-to-severe COPD - Wilson, Robert (Int J Chron Obstruct Pulmon Dis, 2015)
BACKGROUND: Acute exacerbations represent a significant burden for patients with moderate-to-severe chronic obstructive pulmonary disease. Each exacerbation episode is frequently associated with a lengthy recovery and impaired quality of life. Prognostic factors for outpatients that may predict poor outcome after treatment with antibiotics recommended in the guidelines, are not fully understood. We aimed to identify pretherapy factors predictive of clinical failure in elderly (≥60 years old) outpatients with acute Anthonisen type 1 exacerbations. TRIAL REGISTRATION: NCT00656747. METHODS: Based on the moxifloxacin in AECOPDs (acute exacerbations of chronic obstructive pulmonary disease) trial (MAESTRAL) database, this study evaluated pretherapy demographic, clinical, sputum bacteriological factors using multivariate logistic regression analysis, with internal validation by bootstrap replicates, to investigate their possible association with clinical failure at end of therapy (EOT) and 8 weeks posttherapy. RESULTS: The analyses found that the independent factors predicting clinical failure at EOT were more frequent exacerbations, increased respiratory rate and lower body temperature at exacerbation, treatment with long-acting anticholinergic drugs, and in vitro bacterial resistance to study drug. The independent factors predicting poor outcome at 8 weeks posttherapy included wheezing at preexacerbation, mild or moderate (vs extreme) sleep disturbances, lower body temperature at exacerbation, forced expiratory volume in 1 second <30%, lower body mass index, concomitant systemic corticosteroids for the current exacerbation, maintenance long-acting β(2)-agonist and long-acting anticholinergic treatments, and positive sputum culture at EOT. CONCLUSION: Several bacteriological, historical, treatment-related factors were identified as predictors of early (EOT) and later (8 weeks posttherapy) clinical failure in this older outpatient population with moderate-to-severe chronic obstructive pulmonary disease. These patients should be closely monitored and sputum cultures considered before and after treatment.